Acoustic characterization of private lands under payment for environmental services at Golfo Dulce Forest Reserve, Costa Rica - Barrantes-Madrigal, Jimmy (2024)
[Introduction]: In Latin America, the sensitive tropical biodiversity found outside of protected wilderness areas is under threat. In Costa Rica, the payment for environmental services (PSA) represents a mechanism to protect forests on private farms, but it lacks specific indicators on the state of biodiversity and forest conservation. [Objective]: To analyze the use of acoustic monitoring for ecosystem assessment at 11 sites in the Osa Peninsula, nine on private farms, and two sites within Corcovado National Park. [Methods]: Soundscapes were recorded from May 25 to June 1, 2021, using acoustic recorders. It was analyzed the behavior of six acoustic indices at each sampling site and applied an automated detection analysis of vocalizations of two representative bird species of the area. [Results]: It was found that the most fragmented sites presented higher activity, energy, and acoustic diversity, possibly due to edge effects and ecotones present, as well as a high forest component in the surrounding matrix. Automated vocalization detection indicated that the species Hylopezus perspicillatus turned out to be more sensitive to differences in the landscape than Trogon bairdii. [Conclusions]: The use of acoustic indices, although it associates features of the degree of conservation, was not a differentiating element of the quality of the ecosystem in the evaluated farms. The monitoring ofspecies through the detection of their vocalizations was promising. A careful and rigorous sampling design, with moresampling points per site, is recommended to achieve accurate measurements and avoid bias in the analysis.